Ama:nati as a Non-Material Value of Accounting Practices - Thalib, Mohamad Anwar (AKTSAR: Jurnal Akuntansi Syariah, 2022)
This study aims to find the value of local wisdom behind how students majoring in Islamic accounting from the Gorontalo tribe practice accounting. This study uses the Islamic paradigm. The approach chosen is Islamic ethnomethodology. The study results indicate that trust (Amanah) is a non-material value that is the leading spirit of Gorontalo ethnic students practicing accounting. The value of this mandate is reflected in the decisions of students who use educational assistance funds from the government to meet all needs related to supporting their education, such as buying books, paying for boarding houses, and laptops. In the culture of the Gorontalo people, this Amanah value is often advised by the elders through lumadu "openu de moputi tulalo, bo dila moputi baya". It means to be ashamed. The feeling of shame is one of them if the local community cannot maintain their mandate. In Islamic religious law, the value of trust is found in Surah an-Nisa verse 58.